Pengaruh Kemandirian Belajar dan Perhatian Orang Tua Terhadap Prestasi Belajar Matematika - Rita Ningsih; Arfatin Nurrahmah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2016)
This study aims to prove the influence of independent learning and attention of parents towards mathematics achievement. The method used in this research is the analysis method using correlational survey. Samples were obtained by using simple random sampling technique as many as 90 students of class VIII SMP Private Setiabudi sub-district. The data collection is done with using questionnaires and written tests. Data analysis was performed using SPSS 20 is composed of a descriptive analysis, test data analysis requirements, and hypothesis testing. Test requirements analysis of the data used, the normality test, linearity and multicollinearity test. Based on the results of the study it was concluded that: (1) There is a significant positive effect on the independence of learning mathematics achievement; (2) There is a significant positive effect of parental attention to mathematics achievement; and (3) There is a significant positive effect between learning independence and parental supervision of mathematics achievement. Large donations learning independence and parental supervision of mathematics achievement of 45.3% of the remaining 54.7% was contributed by the other variables in addition to independent learning and attention from their parents. Keywords: Independence Learning, Attention Parents, Learning Achievement in Mathematics.